20. századi egyetemes történeti szöveggyűjtemény Interaktív tananyagok a középiskolai és egyetemi történelemoktatásban - Debreczeni, Márk; Hegedűs, Zoltán (Hallgatói Műhelytanulmányok, 2022)
Debreczeni, Márk – Hegedűs, Zoltán: 20th century universal historical text collection – Interactive educational materials for secondary school and university in history education Nowadays, Hungarian teachers and teacher trainees do not really use interactive teaching materials during their history lessons. However, in most school have the opportunity to use smartboards and other technical devices. They delay to make their lessons more interesting and more interactive. We need to change our teaching habits undoubtedly. In this study, we introduce our interactive online teaching material, which made for secondary school students and teachers. Teachers have to adapt new methods, teaching and learning techniques to keep step with the students of the 21st century. Nevertheless, it will be hopefully useful in the teacher-training program at the universities as well. This research introduces the differences and needs of diverse generations and the features of the interactive history textbook. In the MOODLE system, online and digitalized text sources, videos, records, different types of tests are equally used, which are suitable to measure students’ knowledge and skills. It is like an E-book, but other functions make the program more interactive. The whole material focus on the 20th century and divided into six periods. Each era have coherent textbooks and separated tests for practice. Moreover, the program offers multifarious and exciting ways of history learning and teaching.